Ferritin Is a Marker of Inflammation rather than Iron Deficiency in Overweight and Obese People - Abidullah Khan; Wazir Muhammad Khan; Maimoona Ayub; Mohammad Humayun; Mohammad Haroon (Journal of Obesity)
Background. In clinical practice, serum ferritin is used as a screening tool to detect iron deficiency. However, its reliability in obesity has been questioned. Objectives. To investigate the role of ferritin in overweight and obese people, either as a marker of inflammation or iron deficiency. Methods. On the basis of body mass index (BMI), 150 participants were divided into three equal groups: A: BMI 18.5–25 kg/m2, B: BMI 25–30 kg/m2, and C: BMI>30 kg/m2. Serum iron, total iron binding capacity (TIBC), transferrin saturation, ferritin, C-reactive protein, and hemoglobin (Hb) were measured for each participant and analyzed through SPSS version 16. One-way ANOVA and Pearson’s correlation tests were applied. Results. Ferritin was the highest in group C (M=163.48±2.23, P<0.001) and the lowest in group A, (M=152.78±1.81, P<0.001). Contrarily to ferritin, transferrin was the lowest in group C, (M=30.65±1.39, P<0.001) and the highest in group A, (M=38.66±2.14, P<0.001). Ferritin had a strong positive correlation with both BMI (r=0.86, P<0.001) and CRP (r=0.87, P<0.001) and strong negative correlation with Hb, iron, TIBC, and transferrin saturation (P<0.001). Conclusion. Ferritin is a marker of inflammation rather than iron status in overweight and obese people. Complete iron profile including transferrin, rather than serum ferritin alone, can truly predict iron deficiency in such people.